Application of Conferencing Approach to Improve Cooperation Skills of Class IV Elementary School Students - Yoesrina Novia Vini Syafitri; Tatat Hartati; Tatang Tatang (Universitas Sebelas Maret, 2019)
Abstract: The ability of cooperation is an important aspect of personality and needs to be owned by everyone, especially in group learning. Based on the preliminary results of the learning in the fourth grade of CST SDN shows that the ability of student cooperation is still low. This is because the teacher does not give clear instructions about learning in groups, how to learn in groups, how to divide the tasks for each member of his group, and the teacher does not motivate the students to be able to work with friends of his group. This study aims to describe the application of the conferencing approach to improving the ability of cooperation of fourth-grade elementary school students. The research method used is the research of the class action model of Kemmis and Mc Taggart. The subjects of this study were 38 students of grade IV SDN CST. Data collection techniques used were observations and field notes. Qualitative data were taken using techniques from Miles and Huberman which consist of data reduction, data presentation and conclusion, and verification. While the quantitative data is taken using the statistic average and percentage. The results show that the application of the conferencing approach can improve students' cooperative ability, especially on group learning in the classroom.